Isolation and characterization of genes encoding leucoanthocyanidin reductase and anthocyanidin reductase from the green Trung Du tea in Thai Nguyen (Camellia sinensis) - Yen, Hoang Thi Thu; Thanh, Duong Trung; Hang, Pham Thi; Dung, Duong Trung; Hue, Huynh Thi Thu (Vietnam Journal of Biotechnology, 2018)
Catechins are major components of the flavonoid pathway in tea in which they are synthesized in four distinct ways under the direct catalysis of two enzymes, leucoanthocyanidin reductase (LAR)and anthocyanidin reductase(ANR). In this study, we conducted the cloning and sequence analysis of genes encoding ANR and LAR (namely, CsANR2 and CsLAR1) from the Green Trung Du cultivar. The length of CsANR2 gene is 1,014 bp, encoding 337 amino acids. Comparative analysis of the nucleotide sequences showed that there was limited difference between the CsANR2 gene in the green tea cultivar and the CsANR2 sequence published in Genbank, with nucleotide identity of 98.9–99.6%, and amino acid similarity of 95.7–99.5%. CsANR2 has two major functional regions, the N-terminal glycine-rich domain that functions in association with NAD or NADP (GGTGFVAA); the substrate-specific domain has amino acids involved in enzyme catalysis (S130, Y167 and K171). The results showed that the difference in nucleotide sequences does not lead to amino acid change in the important functional domains of CsANR2. The length of CsLAR1 gene is 1,029 bp, encoding 342 amino acids. The difference between CsLAR1 of green Trung Du tea and those published in GenBank ranged from 96.3–100% in nucleotide, and 88.3–100% in amino acid sequence. CsLAR1 contains 3 conserved amino acid motifs among species, RFLP, ICCN and THD. However, the ICCN motif of CsLAR1 from green Trung Du tea has a distinct amino acid from the published sequences (I153T). Analysis of the functional domains of CsLAR1 showed that CsLAR1 in tea was conserved in the amino acids linked to the substrate, and the N-terminal glycine-rich domain binding to NADP has a modified amino acid (GACGFIG). How these amino acid modifications affect CsANR2 and CsLAR1 enzymatic activities, that further research is needed to be conducted for clarification.